Authentic Connections Groups: A Pilot Test of an Intervention Aimed at Enhancing Resilience Among Nurse Leader Mothers. Issue 1 (3rd February 2020) - Chesak, Sherry S.; Bhagra, Anjali; Cutshall, Susanne; Ingram, Alexandra; Benoit, Renee; Medina‐Inojosa, Jose R.; Hayes, Sharonne N.; Carolan, Bridget J.; Luthar, Suniya
Abstract: Background: Nurse leaders who are mothers are at significant risk for experiencing stress, burnout, and occupational fatigue. Authentic Connections (AC) Groups is an intervention shown to be effective for fostering resilience among at‐risk moms, including physicians; however, it has not previously been tested with nurse leaders. Aims: Our aims were to test the feasibility and acceptability of the AC Groups intervention with nurse leader mothers and examine its effects on participant resilience, as measured by increased self‐compassion and decreased distress, depression, perceived stress, and burnout. Methods: A randomized controlled trial design was employed for this pilot study, with 36 nurse leaders at Mayo Clinic. AC participants attended group sessions for an hour per week for 12 weeks. Control group members were provided 1 hr per week of free time over 12 weeks. Multiple self‐report psychological measures were completed at baseline, post‐intervention, and 3‐month follow‐up. Results: The AC Groups intervention was feasible and well‐received by nurse leaders. Session attendance rates averaged 92%. Despite the small n 's, repeated measures of Analysis of Variance showed significantly greater improvements ( p < .05) for participants in the AC Groups than control condition for depression, self‐compassion, and perceived stress, with large effect sizes ( η p 2 0.18–0.22). In addition, effect sizes for anxiety and feeling loved approximated the moderate range ( η p 2 0.05 and .07). Linking Evidence to Action: The AC intervention shows promise as a feasible intervention for mitigating nurse leader mothers' stress by positively impacting indices of well‐being, including depression, self‐compassion, and perceived stress. Given, the prevalence of stress and burnout among nurse leaders, the effectiveness of the AC intervention in fostering resilience in this population has significant implications for research and practice. Further research is warranted with larger numbers from multiple sites, longer follow‐up periods, and biomarker measures of stress.